ACCURACY OF FNAC IN FEMALE BREAST LESIONS - D P, Jethwani; T M, Purohit; M B, Purohit; S H, Gandhi; G A, Dhruva; K, Pujara (International Journal of Clinical and Biomedical Research, 2015)
Background: Various breast lesions are common lesions in females with a wide range of variability from inflammatory lesions, benign and malignant breast lesions. FNAC is first diagnostic test, as it has high sensitivity and specificity. Lesions were categorized on FNA into inflammatory lesions, benign neoplastic lesions, malignant neoplastic lesions, and suspicious for malignancy. Methods: This was a retrospective study done in the Department of Pathology, P.D.U. Medical College, Rajkot, Gujarat State, India from Aug-2013 to July 2014. FNAC of 392 cases of breast lesions were done and reported by expert pathologist. The histopathological specimens when available were reported by other pathologist without prior knowledge of FNA diagnosis. Sensitivity, Specificity and Accuracy of FNA diagnosis were then analyzed. Results: A total of 392 cases of breast lesions were diagnosed on FNA, out of them histopathological correlation was available in 87 cases. Benign breast lesions are more common in younger patients in 21-30 yrs age group and malignant lesions are more common in old age group patients of 41-60 yrs with few exceptions. In our setup fibroadenoma is the most common benign breast lesion (26.53%) and ductal carcinoma (17.86%) is the most common malignant lesion. The sensitivity, specificity and accuracy of FNAC for malignant lesions were found to be 91.43%, 100% and 96.25% respectively. Conclusion: FNAC is an effective and valid tool as the first line diagnostic modality in the preoperative diagnosis of the malignant and benign breast lesions. KEYWORDS: FNAC; Breast lesions; Fibroadenoma; Ductal carcinoma.